2011
DOI: 10.14710/jitaa.36.3.205-212
|View full text |Cite
|
Sign up to set email alerts
|

Milk Quality of Dairy Goat by Giving Feed Supplement as Antioxidant Source

Abstract: Free radical levels can be higher than the level of endogenous antioxidants in the body so that uncomfortable conditions in the body of dairy goats could happen. To anticipate this uncomfortable conditions will be given feed supplement (FS) as source of antioxidants (AOX). FS contain mixture pineapple rind meal and antioxidant minerals (AOXM) each 25 ppm Zn and 10 ppm Cu. This experiment was carried out to investigate the effect of feed supplements as antioxidant source on milk quality of dairy goats. Sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(31 reference statements)
1
14
0
2
Order By: Relevance
“…It is clear that current knowledge is not conclusive regarding the amount of Vitamin E needed to maintain milk quality in terms of SCC or oxidation [ 118 ]. Finally, despite the large number of studies describing the beneficial role of various antioxidants on the quality of milk and its composition, still many researchers reported that dietary antioxidants had no effect on milk protein, lactose, fat, total solids, and non-fat solids of cow’s milk [ 119 ] or goat’s milk [ 120 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…It is clear that current knowledge is not conclusive regarding the amount of Vitamin E needed to maintain milk quality in terms of SCC or oxidation [ 118 ]. Finally, despite the large number of studies describing the beneficial role of various antioxidants on the quality of milk and its composition, still many researchers reported that dietary antioxidants had no effect on milk protein, lactose, fat, total solids, and non-fat solids of cow’s milk [ 119 ] or goat’s milk [ 120 ].…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…There are studies demonstrating the presence of a cholesterol-lowering effect in goats receiving Yucca schidigera powder compared to the control group [17] . Mardalena et al [18] reported that Yucca schidigera powder possesses an anti-oxidant function and this lowered cholesterol by preventing lipid oxidation through its ability to capture free radicals and radical peroxy salts. In this study, while the commercial food containing yucca extract was not seen to have a triglyceride-and cholesterol-lowering effect in cats, other studies suggest that the use of the herb may originate from differences in dosage.…”
Section: Discussionmentioning
confidence: 99%
“…This can affect the quality and health value of animal products (e.g. in Mardalena et al ; Table ) . Without describing the metabolic pathway in digestion, reports of a quality improvement in milk of dairy goats due to a higher ratio of unsaturated fatty acids after curcumin supplement exist .…”
Section: Effects Of Use In Animal Nutritionmentioning
confidence: 99%
“…in Mardalena et al; Table 1). 72 Without describing the metabolic pathway in digestion, reports of a quality improvement in milk of dairy goats due to a higher ratio of unsaturated fatty acids after curcumin supplement exist. 73 Experiments with quails showed a decreased lipid content of eggs after curcumin supplementation.…”
Section: -55mentioning
confidence: 99%